2005
DOI: 10.1007/s00442-005-0310-2
|View full text |Cite
|
Sign up to set email alerts
|

Nest site attributes and temporal patterns of northern flicker nest loss: effects of predation and competition

Abstract: To date, most studies of nest site selection have failed to take into account more than one source of nest loss (or have combined all sources in one analysis) when examining nest site characteristics, leaving us with an incomplete understanding of the potential trade-offs that individuals may face when selecting a nest site. Our objectives were to determine whether northern flickers (Colaptes auratus) may experience a trade-off in nest site selection in response to mammalian nest predation and nest loss to a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 49 publications
1
77
2
1
Order By: Relevance
“…Generally, most of the studies on nest site selection have failed to take into account more than one source of nest loss, which limits our understanding on the complexity of cues affecting algorithms of nest site choice in birds (Fisher and Wiebe 2005). As one of the exceptions, the study of Coulson (1968) demonstrated that the competition for good-quality nesting sites was substantially intensified in the centre of a Blacklegged Kittiwake colony when compared with the peripheral zones.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, most of the studies on nest site selection have failed to take into account more than one source of nest loss, which limits our understanding on the complexity of cues affecting algorithms of nest site choice in birds (Fisher and Wiebe 2005). As one of the exceptions, the study of Coulson (1968) demonstrated that the competition for good-quality nesting sites was substantially intensified in the centre of a Blacklegged Kittiwake colony when compared with the peripheral zones.…”
Section: Discussionmentioning
confidence: 99%
“…in the northern flicker Colaptes auratus (e.g. Lawrence 1967, Moore 1995, Fisher & Wiebe 2005, great spotted woodpecker (proportions of multi-cavity trees between 8%-49%; HĂ„gvar et al 1990, Hansson 1992, Glue & Boswell 1994, Stenberg 1996, Mazgajski 1998, and black woodpecker (25%-47%; HĂ„gvar et al 1990, Rolstadt et al 2000, KosiƄski et al 2011. Nest tree reuse has been occasional or absent in the three-toed woodpecker in central Europe (Pechacek 2001, Pechacek & d'Oleire-Oltmanns 2004, P. Pechacek pers.…”
Section: Cavity and Tree Reuse Patterns In The Three-toed Woodpecker mentioning
confidence: 99%
“…The suitability of potential nest sites is also based on the prospects offered of avoiding predation and maximisation of reproductive success for cavity-nesting birds. The choice of nest sites by cavity-nesting birds is often influenced by factors such as the height above the ground, vegetal concealment of entrances of cavities, and neighbouring vegetation type due to edge effects (Fisher & Wiebe 2005). Site-choice may be further influenced by competition.…”
Section: Conservation Implicationsmentioning
confidence: 99%